Communities of Print
1 online resource.
Keywords: This book provides a new perspective on book history by exploring communities created by the production and consumption of printed material. Essays by leading scholars explore the connections between writers, printers, booksellers and readers and examine changes and continuities across the period 1500 to 1800. As well as investigating the networks behind the production and dissemination of printed material, this collection examines the ways in which readers consumed, used and shared their printed texts. By focusing on the materiality of early modern texts, contributors to this volume offer new interpretations of the history of reading, the book trade, and the book as an object in early modern Europe.